2012
DOI: 10.1177/0961203312469259
|View full text |Cite
|
Sign up to set email alerts
|

Safety profile of belimumab: pooled data from placebo-controlled phase 2 and 3 studies in patients with systemic lupus erythematosus

Abstract: Safety data were pooled and analyzed from one phase 2 and two phase 3 double-blind, placebo-controlled, repeat-dose systemic lupus erythematosus (SLE) trials of belimumab 1, 4 (phase 2 only), and 10 mg/kg. Types and rates of adverse events (AEs) were similar across treatment groups. Rates of patients experiencing any serious AE were 16.6%, 19.5%, 13.5%, and 18.0% with placebo, and belimumab 1, 4, and 10 mg/kg, respectively; rates of serious infusion reactions (including hypersensitivity reactions) occurring on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
2
15

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 27 publications
6
68
2
15
Order By: Relevance
“…The percentage of patients experiencing AEs was lower in the open-label pSS trial than in SLE trials (54% of pSS patients versus 93% of SLE patients), which might be due to the larger percentage of SLE patients receiving co-treatment with immunosuppressants. [111,112] A 52-week extension study of belimumab treatment in 19 pSS patients did not show any additional serious AEs or infusion reactions. [113] In summary, belimumab is effective and well tolerated in SLE.…”
Section: Belimumabmentioning
confidence: 93%
“…The percentage of patients experiencing AEs was lower in the open-label pSS trial than in SLE trials (54% of pSS patients versus 93% of SLE patients), which might be due to the larger percentage of SLE patients receiving co-treatment with immunosuppressants. [111,112] A 52-week extension study of belimumab treatment in 19 pSS patients did not show any additional serious AEs or infusion reactions. [113] In summary, belimumab is effective and well tolerated in SLE.…”
Section: Belimumabmentioning
confidence: 93%
“…Uygulama esnasında veya uygulamadan birkaç saat sonra ciddi/hayatı tehdit edici seviyede hipersensitivite ve infüzyon reaksiyonları (anafilaktik reaksiyonlar, bradikardi, hipotansiyon, anjiyoödem, dispne) görülebilir. Bu etkilerin görülme sıklığı klinik çalışmalarda %1'in altında saptanmıştır (42). Raş, bulantı, miyalji, başağrısı gibi gecikmiş tip, akut olmayan semptomlar da oluşabilir.…”
Section: Türk Nefroloji Diyaliz Ve Transplantasyon Dergisi Turkish Neunclassified
“…The rate of adverse events ranged from 6 to 38% [Ginzler et al 2014;Wallace et al 2013;Andreoli et al 2014] and included infusion reactions, hypersensitivity, headache, nausea and fatigue, in addition to infections as mentioned above. Over 16% of patients were reported to have a psychiatric adverse event while on belimumab by Wallace and colleagues [Wallace et al 2013], which is higher than the reported rates with standard SLE therapy alone. Over half of those experienced insomnia or anxiety; however, there were 6% of the patients who experienced severe depression and 0.1% reported suicidal ideation while on belimumab.…”
Section: Adverse Eventsmentioning
confidence: 99%